Socialization of Clean Water Improvement Program with Filterization Method to Improve Public Health RT 06 RW 01 Jambenenggang Village, Sukabumi Regency (Group 8 Health Division) - Yepi Sopian; Siti Rahmawati; Yuni Sri Wahyuni; Risvi Septiani; Siti Sarah; Sipa Yeni (Indonesian Journal of Society Development, 2023)
The problem of clean water is the basic problem of our life. We need clean water every day for bathing, washing, etc. Of course, access to clean water makes our lives healthier, but clean water is a scarce commodity nowadays. As in Jambenenggang Village, Kebonpedes District, Sukabumi Regency. Most of the Jambenenggang people still use river water for bathing and washing. To overcome this problem, an alternative solution to ensure that the water wells for RT/RW 01/06 meet the physical, chemical and bacteriological requirements is to purify the well water using the filtration method. The material is suspended in water through a porous medium. With the help of this useful function, purifying river water using the filter method allows river water in RT/RW 01/06 to meet physical, chemical and bacteriological requirements